2022
DOI: 10.1093/mnras/stac3775
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic optical polarization of BL Lac: while faint and bright

Abstract: Due to the first results on astrophysical X-ray polarization provided by IXPE observatory, the interest in wavelength-dependent synchrotron polarization of BL Lac type objects increases. This paper presents the results of multi-band optical observations of the well-known blazar named BL Lac (z = 0.069) in polarized light. It was shown that the object’s emission, regardless of its phase of activity, is characterized by the intraday variability of brightness and polarization with changes occurring on a time-scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The comparison reveals a good correlation between the optical and γ-ray LCs. In general, the LCs could be split visually into two parts-a preflare and a flare (see also Shablovinskaya et al 2023).…”
Section: Short-term Variabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…The comparison reveals a good correlation between the optical and γ-ray LCs. In general, the LCs could be split visually into two parts-a preflare and a flare (see also Shablovinskaya et al 2023).…”
Section: Short-term Variabilitymentioning
confidence: 99%
“…In a recent study, Kalita et al (2023) reported results from the BL Lacertae monitoring from 2020 October 1 to November 23 in the optical. According to their Table 2, the source showed INV during 4 nights out of 10 (the probably variable cases considered nonvariable); see also Shablovinskaya et al (2023) regarding the source monitoring in that period. Therefore, the duty cycle could be estimated as ∼40%, which is significantly lower than ours.…”
Section: Emitting Region Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…BL Lacertae has been of great interest for numerous intense multiwavelength (MWL) campaigns (e.g. Villata et al 2002Villata et al , 2003Böttcher et al 2003;Raiteri et al 2010;Wierzcholska et al 2015;Agarwal et al 2017;MAGIC Collaboration et al 2019;Weaver et al 2020;Jorstad et al 2022;Kalita et al 2023;Shablovinskaya et al 2023); in particular, BL Lacertae is one of the favorite targets of the campaigns organized by the Whole Earth Blazar Telescope collaboration. More than century-long observations of BL Lacertae reveal intense variability on diverse timescales ranging from a few minutes (e.g.…”
Section: Introductionmentioning
confidence: 99%